Coordination-driven assembly of a supramolecular square and oxidation to a tetra-ligand radical species. Issue 43 (8th May 2019) - Herasymchuk, Khrystyna; Miller, Jessica J.; MacNeil, Gregory A.; Sergeenko, Ania S.; McKearney, Declan; Goeb, Sébastien; Sallé, Marc; Leznoff, Daniel B.; Storr, Tim
Abstract : The design and synthesis of a supramolecular square was achieved by coordination-driven assembly of redox-active nickel(ii ) salen linkers and (ethylenediamine)palladium(ii ) nodes. Abstract : The design and synthesis of a supramolecular square was achieved by coordination-driven assembly of redox-active nickel(ii ) salen linkers and (ethylenediamine)palladium(ii ) nodes. The tetrameric geometry of the supramolecular structure was confirmed via MS, NMR, and electrochemical experiments. While oxidation of the monomeric metalloligand Schiff-base affords a Ni(iii ) species, oxidation of the coordination-driven assembly results in ligand radical formation.